Analysis of Legal Framework Surrounding Absentee Land Ownership Post-Inheritance (Case Study in Indramayu Regency) - Dina Apriliani Rahayu; Asmarani Ramli (Faculty of Law, Universitas Negeri Semarang, 2024)
Indramayu Regency has become increasingly concerned about absentee land ownership, or the ownership of agricultural land by people who do not live nearby, especially after inheritance events. This approach is at odds with the regulations designed to guarantee that the outcomes of land management are accessible to the local community. This study seeks to identify and examine the factors contributing to absentee land ownership practices following inheritance in Indramayu Regency, as well as the legal ramifications associated with these practices in the same region. The study employs a qualitative methodology, drawing on a juridical-empirical approach. The results show that the social factors that lead to absentee land ownership after inheritance in Indramayu Regency are the community's lack of legal knowledge and cultural norms that protect and allow this practice without meaning to. From an economic standpoint, the heirs' consideration of absentee land as an investment and a security for their retirement plays a significant role. Given the rights and responsibilities of the heirs of absentee landowners, the legal consequences of absentee land ownership practices following inheritance indicate that the heirs have a rightful claim to the inherited land. When land is designated as absentee land, the heirs must transfer it to another individual living in the district where the land is situated within one year following the testator's death. The heir's failure to adhere to the prohibition ultimately results in a legal conflict.